Taxation as a real incentive for land conservation - Browne, Richard Arthur (Department of Finance and Tax, 2014)
The objective of the dissertation is to investigate the opportunity to apply taxation incentives to promote land conservation in South Africa. This dissertation was conducted by means of a critical analysis of current legislation and data available in search of a suggested solution to finding appropriate tax incentives to encourage land conservation. In order to limit the scope of the research, a number of assumptions were made. Conflicting viewpoints underlying certain of these assumptions are discussed.